Suplementasi Tepung Daun Kelor (Moringa oleifera) Sebagai Sumber Karotenoid Terhadap Tingkat Kecerahan Warna, Laju Pertumbuhan, dan Sintasan Benih Ikan Koi - Dahlia; Ardiansyah; Agnes Pratiwi (Jurnal Galung Tropika, 2023)
This study aims to determine the effect of supplementation with Moringa oleifera leaf flour as a source of carotenoids on the level of color brightness, growth rate, and survival of koi fish seeds (Cyprinus rubrofuscus). The research design was a Completely Randomized Design (CRD), with 4 treatments and 3 replications. Treatments A (without Moringa leaf flour supplementation), B (100 grams Moringa leaf flour supplementation/kg feed), C (200 grams Moringa leaf flour supplementation/kg feed), and D (300 grams Moringa leaf flour supplementation/kg feed). The results of the study showed that supplementation with Moringa leaf flour as a source of carotenoids in feed, although it did not (yet) have a significant effect on the color brightness of koi fish seeds (P>0.05) because the dose given was thought to be still insufficient, had a significant effect on absolute growth and survival to Koi fish seeds (P<0.05). It can be concluded that Moringa leaf flour can be used as an alternative supplement source of carotenoids to increase the brightness of koi fish color. However, the correct and optimal dosage still needs further research.